2021
DOI: 10.1038/s41598-021-94542-5
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 molecular diversity in Brazil unveiled by 10 years of sampling by the national genotyping network

Abstract: HIV-1 has diversified into several subtypes and recombinant forms that are heterogeneously spread around the world. Understanding the distribution of viral variants and their temporal dynamics can help to design vaccines and monitor changes in viral transmission patterns. Brazil has one of the largest HIV-1 epidemics in the western-world and the molecular features of the virus circulating in the country are still not completely known. Over 50,000 partial HIV-1 genomes sampled between 2008 and 2017 by the Brazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Previous studies demonstrate that the expanding HIV-1 subtype B epidemic in the Northern Brazilian state of Amazonas was driven by both pandemic (B PAN ) and non-pandemic (B CAR ) viral variants ( Cabello et al, 2015 ; Divino et al, 2016 ; Arantes et al, 2019 ; Crispim et al, 2019 ; Chaves et al, 2021 ; Gräf et al, 2021 ), thus creating a great opportunity to compare the epidemic dynamics of both subtype B forms spreading in the same population. This study revealed that the B PAN and B CAR epidemics in Amazonas have been shaped by different evolutionary histories, but displayed very similar transmissibility and expansion dynamics at most recent times.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies demonstrate that the expanding HIV-1 subtype B epidemic in the Northern Brazilian state of Amazonas was driven by both pandemic (B PAN ) and non-pandemic (B CAR ) viral variants ( Cabello et al, 2015 ; Divino et al, 2016 ; Arantes et al, 2019 ; Crispim et al, 2019 ; Chaves et al, 2021 ; Gräf et al, 2021 ), thus creating a great opportunity to compare the epidemic dynamics of both subtype B forms spreading in the same population. This study revealed that the B PAN and B CAR epidemics in Amazonas have been shaped by different evolutionary histories, but displayed very similar transmissibility and expansion dynamics at most recent times.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used a total of 1,272 HIV-1 subtype B pol sequences (nucleotides 2,253–3,275 of reference strain HXB2) from Amazonas state sampled between 2009 and 2018 that were either available at the Los Alamos HIV Database 1 by March 2021 or were recently published ( Chaves et al, 2021 ; Gräf et al, 2021 ) and made available in GenBank 2 . Only one sequence per subject was selected.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…the presence of CRF31_BC and CRF02_ AG in pregnant women suggests a recent introduction and dissemination of these recombinant forms, originating respectively from African countries and southern Brazilian states [10]. Phylogenetic analysis of HIV-1 genotyping sequences proved to be eff ective in studying the molecular epidemiology of HIV-1 in Brazil [11,12].…”
Section: Discussionmentioning
confidence: 99%